Ozonoterapia na Osteoartrose do Joelho - NOVA Medical School|Faculdade de Ciências Médicas (NMS|FCM); Centro de Estudos de Doenças Crónicas (CEDOC) (2018)
INTRODUCTION: The aim of this study was to conduct a systematic review in order to examine the effectiveness of ozone therapy on knee osteoarthritis. The objectives were to evaluate the effect over time of ozone therapy in terms of knee pain, functional improvement and radiographic progression. MATERIAL AND METHODS: A search was carried out on PubMed, Embase, Cochrane Library, Scopus and Web of Science databases to identify randomized and controlled studies focusing on this association. The following descriptors were used in English: ozone therapy, knee osteoarthritis. A descriptive summary and quality assessment was made of all studies included for analysis. RESULTS: Six randomized and controlled studies were identified. The risk of bias assessment demonstrated that one study was considered as having a moderate risk of bias and the remainder a high risk of bias. No quantitative analysis of the data was performed, as the studies included were not sufficiently homogeneous. The participants in the studies were generally elderly patients with mild to moderate knee osteoarthritis. DISCUSSION: The variability of ozone therapy and the comparators demonstrates that there is no standardized therapy. Few studies reported adverse effects, and where they occurred, they were mild and associated with the procedure. CONCLUSION: Ozone therapy proved effective in the short-term in relation to placebo and when combined with hyaluronic acid, but it was not superior to other current treatments. More randomised and controlled studies are needed to evaluate the risks/benefits of ozone therapy, both in the short term and the medium/long term.